Hepatoprotective and antioxidant potential of Nyctanthes arbor-tristis L. leaves against antitubercular drugs induced hepatotoxicity - Sachin Chaudhary; Ramesh K. Gupta; Amit Kumar; Hamadeh Tarazi (GarVal Editorial Ltda., 2018)
Context: Nyctanthes arbor-tristis L. (Oleaceae) leaf are used in treatment of malaria, rheumatoid arthritis, chronic fever and enlargement of spleen; however, there is paucity of information on its hepatoprotective and antioxidant potential. Aims: To evaluate hepatoprotective and antioxidant potentials of ethanolic leaf extract of Nyctanthes arbor-tristis L. Methods: After collection and authentication of the vegetal material, ethanolic extract was collected. The combination of antitubercular drugs (isoniazid, rifampicin and pyrazinamide) was used to induce hepatotoxicity in Wistar rats. Hepatoprotective effect was evaluated at doses 125, 250 and 500 mg/kg, body weight by estimating the activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and levels of total bilirubin (TBL). The effects on lipid peroxidation (LPO), reduced glutathione (GSH) and catalase (CAT), superoxide dismutase (SOD) were estimated. Docking study was conducted to anticipate the probable biological targets associated with its hepatoprotective effect. Results: The plant extract dose of 500 mg/kg, body weight significantly declined the levels of AST, ALT, ALP and TBL at (p < 0.001), which is approximately corresponding to the dose of reference compound silymarin and reversed the levels of LPO, GSH, SOD, CAT as compared to silymarin dose. Histopathological studies revealed regeneration of hepatocytes. The docking results suggested that some active constituents of plant leaves potentially interact with human pregnane X receptor, human constitutive androstane receptor and the farnesoid X receptor. Conclusions: The extract of Nyctanthes arbor-tristis L. remarkably possesses hepatoprotective and antioxidant effect and evinced its traditional claim. Future studies should be done to isolate active phytoconstituents for use in drug discovery.